Translating picture books: towards a multimodal approach - Abdullah Sherif (Insights into Language, Culture and Communication, 2022)
Children's picture books are complex multimodal texts. Meaning is created when modes interplay with each other. As a multimodal text, the author and the illustrator play a role in the utilization of semiotic resources, whether verbal or visual. The study of multimodality in translation studies acknowledges this. Yet, current translational practices remain inadequate for the description and analysis of translated children's picture books. Despite that, a call for interdisciplinary research in both fields has been established. This call expands the scope of translation by examining past and current practices and describing them. This paper aims to consolidate the translation of children's picture books from a multimodal perspective dedicated to children's picture books. Furthermore, it calls for an integration of multimodality into translation studies as translation is the transfer of meaning contained in semiotic modes.